Economics of the Canadian corporate bond market - Peters, J. Ross. (Montreal : McGill-Queen's University Press, 1971)
This book defines and describes the new issue market for privately placed and publicly offered corporate debt securities in Canada.
Bibliography: p. 119-123.
ucj 18/01/2019
Loans
Keywords: Bonds; Bonds; Bond market